Nicotine conjugate vaccine: is there a right to a smoking future? - Hasman, A. (Journal of medical ethics, 2004)
Tobacco consumption is believed to be one of the world’s greatest preventable health problems. According to the World Health Organisation, 1.1 billion people worldwide are addicted to nicotine with tobacco causing an estimated four million premature deaths every year. The development of a nicotine conjugate vaccine suggests that immunisation may hold promise as a future therapeutic and preventive strategy for tobacco smoking and nicotine addiction. Allowing parents to immunise their children against smoking could be an infringement of children’s right to an open future, however, and is not ethically unproblematic